Peculiarities of the Epidemiological Situation on Tick-Borne Viral Encephalitis in the Russian Federation in 2017 and the Forecast for 2018 - A. Ya. Nikitin; E. I. Andaev; A. K. Noskov; N. D. Pakskina; E. V. Yatsmenko; E. V. Verigina; S. V. Balakhonov (Проблемы особо опасных инфекций, 2018)
The article presents the analysis of tick-borne encephalitis (TBE) epidemiological situation in the Federal Districts of Russia in 2017. Studied has been the effect of causative factors of epidemic process dynamics, such as: rate of people seeking medical help due to tick bites, contamination of ticks with the TBE virus revealed by immune-enzyme analysis and polymerase chain reaction, amount of people who were vaccinated, scope of emergency prophylaxis, the size of treated areas, and amount of funding for TBE-incidence decrease. Authors presented the incidence forecast for the endemic areas as regards TBE, as well as for the whole country for 2018, taking into account the presence or absence of change in its trends during 2008–2017. The values of the confidence interval are 95 % of the indicator fluctuations. Further gradual improvement of the epidemiological situation is expected.